The Use of Modality in Biden’s Dnc Speech 2020: An Interpersonal Metafunction Analysis - lysbeth sirait (Prodi Sastra Inggris UKI, 2023)
This study is aimed to describe and analyze the interpersonal meaning of Biden’s DNC speech in 2020. From the perspective of interpersonal meaning, the users of language establish and maintain their position in the social relationship. This study focuses on the analysis of the usage of modality and the value of modality in expressing interpersonal meaning. This study was conducted by using qualitative. The theory applied in this study is Interpersonal meaning from the Systemic Functional Linguistics (SFL) by M.A.K. Halliday and supported by other Systemic Functional Linguists’ theories. The results of this research showed that the high value of modality is applied in the texts in order to convince the listeners to vote for him, and to show status, power, relationship among them. Key words: interpersonal meaning, modality, SFL(Systemic Functional Linguistics), DNC (Democratic National Committee)